Is there any interaction between real earnings management and accrual-based earnings management? - Vogy Gautama Buanaputra (Jurnal Akuntansi dan Auditing Indonesia, 2021)
This research aims to investigate whether firms employ real earnings management (REM) and accrual-based earnings management (AEM) as substitutes for each other when managing earnings to meet earnings benchmarks. It specifically looks at the sequential nature of both forms of earnings management. REM is proxied by an abnormal amount of operating cash developed by Dechow et al. (1998), while AEM is proxied by the discretionary accrual model by Dechow, Sloan, & Sweeney (1995). The data was obtained from the Economics and Business Data Center, Faculty of Economics and Business, Gadjah Mada University, focusing on manufacturing and mining companies during the period from 2005 to 2013, which resulted in 754 firm-years data. Using correlation tests and an empirical model developed by this research, which captures the interaction between REM and AEM, this research shows that firms use both forms of earnings management sequentially; managers more often engage in accrual-based earnings management if the earnings produced by real manipulations do not meet the earnings target. This finding is important as REM and AEM occur sequentially instead of simultaneously, and earnings performance is not only driven by accrual-based earnings management but also by real earnings management.